Mathematical modelling of Neospora caninum infection in dairy cattle and domestic dogs - Bergero, Paula Elena (2024)
Bovine neosporosis is a global disease caused by the protozoan parasite Neospora caninum. It is a major contributor to abortions in both dairy and beef cattle, resulting in significant economic losses annually. Domestic dogs and certain species of wild carnivores serve as definitive hosts, shedding oocysts into the environment through feces. Two primary transmission mechanisms have been identified: horizontal transmission, occurring through the ingestion of raw or undercooked meat containing cysts or water contaminated with oocysts, and vertical or transplacental transmission, where tachyzoites pass to the fetus. In cattle, the disease exhibits two epidemiological manifestations: endemic and epidemic abortions, known as abortion storms. Dynamic models of infectious diseases have proven valuable for studying dynamic effects and evaluating various control strategies. In this study, we present a compartmental model for neosporosis in both dairy cattle and the domestic dog population. The cattle disease submodel categorizes the population based on the infection mechanism (congenital or acquired through ingestion) to more accurately describe the two epidemiological patterns of the disease. The dog disease submodel represents disease transmission in this host, including infected cattle as a source of infection. A third submodel accounts for environmental contamination with oocysts, acting as a source of infection for cattle. Our goal was to provide a more realistic description of transmission in dairy farms by considering the complete life cycle of N. caninum.